Biothermodynamic Analysis of Caenorhabditis elegans: Model of Growth and Metabolism Based on Empirical Formulas, Metabolism Reactions, and Thermodynamic Properties of Living Matter and Metabolism - Marko E. Popović; Marta Popović; Dong Pei (Biophysica, 2025)
Caenorhabditis elegans is among the most important model organisms. It has been extensively studied from the perspective of life and biomedical sciences. However, no model of growth and metabolism of C. elegans is available in the literature that is based on biothermodynamics and bioenergetics. Such a model would provide insight into growth and metabolism of C. elegans from the perspective of the fundamental laws of nature. In this research, a chemical and thermodynamic characterization of C. elegans is performed, with the determination of empirical formulas, thermodynamic properties of living matter, reactions of biosynthesis, catabolism and metabolism, thermodynamic properties of biosynthesis, catabolism and metabolism, and phenomenological coefficients. Based on the determined properties, a model of the growth and metabolism of C. elegans is developed. The model is used to discuss the metabolism of C. elegans from the aspect of physical chemistry.